The different twins - Stella Gianfreda; Benedetta Carlotti (Italian Political Science, 2018)
According to several scholars, the politicization of issues connected to immigration and the European Union (EU) has generated a new cleavage that now structures political competition in Western Europe. Italy is an interesting case for studying this process, as two ‘different’ populist-Eurosceptic parties, namely the Northern League (LN) and the Five Star Movement (M5S), significantly increased their share of votes in the last round of national elections and eventually managed to form a governmental coalition by politicizing these two issues. This paper proposes a multifaceted conceptualisation of the EU and immigration issues in order to investigate how LN and M5S position themselves across their multiple sub-dimensions. The empirical analysis is based on an original dataset of parliamentary speeches delivered by the two parties’ representatives in two distinct institutional arenas: the Italian one and the European Parliament. The results show that LN’s positions are guided by cultural-identitarian and sovereignist arguments, while M5S mobilizes the two issues to boost its anti-elitist claims. Therefore, the paper claims that the governmental coalition between the two parties is driven by office-seeking motivations, rather than by a policy-seeking strategy.